2011
DOI: 10.1007/s00167-011-1691-x
|View full text |Cite
|
Sign up to set email alerts
|

Articular cartilage of the posterior condyle can affect rotational alignment in total knee arthroplasty

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 27 publications
3
50
2
Order By: Relevance
“…, respectively (12). Our measurement method differs entirely from previously reported methods, although the differences between these CTAs in other reports were very close to our findings (13,14).…”
Section: The Journal Of Medical Investigation Vol 64 February 2017supporting
confidence: 84%
“…, respectively (12). Our measurement method differs entirely from previously reported methods, although the differences between these CTAs in other reports were very close to our findings (13,14).…”
Section: The Journal Of Medical Investigation Vol 64 February 2017supporting
confidence: 84%
“…Given the consistency of the MRI measurements in our study with cadaveric measurements in their study, validation for the use of MRI as a measurement tool for articular cartilage thickness is provided. Tashiro et al [19] showed that the articular cartilage thickness of the posterior condyles can affect rotational alignment in TKA. In their study, failure to account for articular cartilage of the posterior condyles led to excessive external rotation of the femoral components [19].…”
Section: Discussionmentioning
confidence: 99%
“…Tashiro et al [19] showed that the articular cartilage thickness of the posterior condyles can affect rotational alignment in TKA. In their study, failure to account for articular cartilage of the posterior condyles led to excessive external rotation of the femoral components [19]. Consequently, instrumentation and prosthetic knee designs should be based on MRI rather than CT to provide the most accurate anatomic relationships.…”
Section: Discussionmentioning
confidence: 99%
“…One report quantified that the cartilage depicted in MRI showed almost the same thickness as the actual specimens cut intraoperatively, indicating the superior precision that MRI provides when examining the axial anatomy of the distal femur. 27 Nonetheless, there are several limitations to our study. We focused on biomechanical and radiographic outcomes, and it was out of the scope of this project to correlate the predicted rotation from the PSI scan with the actual postoperative femoral rotation or clinical outcomes.…”
Section: Discussionmentioning
confidence: 91%